Задача идентификации по финальному наблюдению для многомерного нелинейного стационарного уравнения квазиоптики с чисто мнимым коэффициентом в нелинейной части - Ибрагимов, Н.С. (Проблемы управления и информатики, 2012)
Розглянуто задачу визначення комплекснозначного коефіцієнта багатовимірного стаціонарного рівняння квазіоптики з чисто уявним коефіцієнтом у нелінійній частині цього рівняння. Доведено теореми існування та єдиності розв’язку задачі ідентифікації. Для її розв’язання встановлено необхідну умову у вигляді варіаційної нерівності. The problem of determining the complex-valued coefficient of a multidimensional nonlinear stationary equation of quasi-optics with the purely imaginary coefficient in the nonlinear part of the equation is considered. The theorems of existence and uniqueness of the solution of the identification problem are proved. The necessary condition in the form of a variational inequality for the solution of the identification problem is established.